Microwave Assisted Efficient Synthesis of Some Flavones for Antimicrobial and ADMET Studies - Rahim, M. A.; Bhuiayan, M. M. H.; Matin, M. M. (Journal of Scientific Research, 2020)
Microwave (MW) assisted synthetic technique was applied for the preparation of chalcone derivatives 5-7 employing Claisen-Schmidt condensation between 2-hydroxyacetophenone and aromatic aldehydes. These chalcones were further subjected to oxidative cyclization via MW irradiation and furnished the related flavones 8-10 which were characterized by FT-IR, 1H and 13CNMR spectra. The use of these MW assisted reactions provided higher productivity (92-98%) in shorter reaction time (2-6 min) with eco-friendly mild reaction conditions and hence found to be a convenient method as compared to conventional synthesis. These chalcones 5-7, and flavones 8-10 were screened for in vitro antimicrobial activities against five bacterial and three fungal pathogens. The study indicated that they were more active against fungal pathogens than that of bacterial organisms and comparable to the standard antifungal antibiotic nystatin. Interestingly, the prediction of activity spectra for substances (PASS) was also found in agreement with the in vitro results. Some of the compounds were found to have good ADMET properties.